Interactions of Dnd proteins involved in bacterial DNA phosphorothioate modification - Xiong, Wei; Zhao, Gong; Yu, Hao; He, Xinyi (Frontiers in Microbiology, 2015)
DNA phosphorothioation (PT) is the first discovered physiological DNA backbone modification, in which a non-bridging oxygen atom of the phosphodiester bond is replaced with a sulfur atom in Rp (Rectus for plane) configuration. PT modification is governed by a highly conserved gene cluster dndA/IscS-dndBCDE that is widespread across bacterial and archaeal species. However little is known about how these proteins coordinately react with each other to perform oxygen–sulfur swap. We here demonstrated that IscS, DndC, DndD and DndE formed a protein complex of which the molecular ratio for four proteins in the complex is approximate 1:1:1:1. DndB here displayed little or weak affinity to the complex and the constructs harboring dndACDE can confer the host in vivo PT modification. Using co-purification and pull-down strategy, we demonstrated that the four proteins assembly into a pipeline in collinear to its gene organization, namely, IscS binding to DndC, DndC binding to DndD, and DndD binding to DndE. Moreover, weak interactions between DndE and IscS, DndE and DndC were also identified.